Systematic fixed income : an investor's guide - Richardson, Scott (Accounting professor) (John Wiley & Sons, Inc., 2022)
"Systematic Fixed Income lays out a framework for identifying the relevant sources of risk and return in public fixed income markets. After a comprehensive analysis of the strategic and tactical roles that fixed income can play in asset allocation, author Scott Richardson covers the systematic return sources for rate and credit sensitive fixed income assets across developed and emerging markets. Armed with an understanding of return drivers, Richardson then explores the implementation challenges (e.g., liquidity, risk) that need to, and can, be overcome to successfully build a systematic fixed income portfolio. Putting it altogether, institutional investors and asset managers will appreciate the powerful diversifying potential of a well implemented systematic fixed income allocation"--